Tykes, Toddlers, Teens, and Twins of Robust Mothers: Do the Offspring of Twinning Mothers Share in Their Mother's Robust Phenotype?. (3rd April 2018) - Chernenko, Alla; Hollinghshaus, Michael; Robson, Shannen; Hanson, Heidi A.; Smith, Ken R.
ABSTRACT: Women who bear twins may possess a robust phenotype compared to non-twinning mothers. We examine mortality patterns for the singleton offspring of mothers of twins compared to the offspring of non-twinning mothers to determine whether they share the hypothesized robust phenotype of their mothers. Using data from the Utah Population Database, we show that both male and female singleton offspring of twinning mothers experience a survival disadvantage prior to age 5, no survival benefit or penalty between ages 5 and 49, and—for males only—a statistically significant survival advantage after age 50. We further examine the survival effects on singletons born before and after a twinset. We observe a survival disadvantage in early life for singleton offspring of twinning mothers born after the twinset for both sexes. In addition, we find a significant survival advantage at older ages in certain categories of male singleton offspring—a likely reflection of mortality selection. The findings suggest that while bearing twins may reflect a robust maternal phenotype, the toll of bearing twins may disadvantage subsequent offspring, especially during infancy.